Աբդուլ Համիդ II ներքին քաղաքականությունը և դրա լուսաբանումը թուրքական պատմագրության մեջ (ուրվագիծ) - Տաթևիկ Հակոբյան (ՀՀ ԳԱԱ հրատ.)
33-летнее правление Абдулa Гамида II является одним из самых противоречивых периодов османской истории, анализ которого продолжает оставаться в сфере интересов не только турецких, но и иностранных исследователей. Abdul Hamid II’s 33-year reign was one of the most contradictive periods of the Ottoman history which analysis is still within the frame of interest of not only Turkish, but also foreign scholars.
Keywords: History; Modern History; D History